A time-resolved fluoroimmunoassay for assessing rabies antibody titers in the sera of vaccinated human subjects. (November 2020) - Bian, Lun; Zhao, Hui; He, Chunhui; Fang, Haolin; Chen, Zhenhua; Lin, Li; Ye, Ke; Wu, Yingsong; Lin, Guanfeng
Abstract: Several studies have investigated the use of simple in vitro tests for the assessment of rabies antibody titers in serum samples from vaccinated human subjects, which would allow the effectiveness of rabies vaccination to be conveniently evaluated. To this end, a novel time-resolved fluoroimmunoassay (TRFIA) for the assessment of rabies antibody titers was established in this study for evaluating the effectiveness of protection against rabies. The TRFIA had a satisfactory limit of detection value (0.035 IU/mL) under optimal conditions. Additionally, the application of the TRFIA was demonstrated in 68 serum samples with satisfactory results. The coefficient variations (CVs) were all <10%, and the recoveries were in the range of 90–110%. The correlation coefficient of titer values obtained using the present TRFIA and the rapid fluorescent focus inhibition test (RFFIT) was 0.733, with a coincidence rate regarding the evaluation results (protected or not protected by vaccination) of 100%. The preliminary results confirmed that the TRFIA had a higher performance than an enzyme-linked immunosorbent assay (ELISA), and could potentially replace the ELISA. Based on these results, the novel TRFIA appears to be a convenient tool for the evaluation of rabies vaccination results based on serum samples from vaccinated human subjects. Highlights: A novel in vitro test for rabies antibody titers in the sera of vaccinated human subjects. Application is demonstrated in practical samples, with satisfactory results. Gets the advantages of simple operation, high stability and excellent accuracy than conventional ELISA method.